DOUBLE DISPERSION RELIES ON COMBINED CONVECTION IN A FLUID WITH VARIABLE PROPERTIES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The present study is to investigate the influence of the variable properties and double dispersion on mixed convection flow over a vertical plate embedded in a power-law fluid saturated porous medium. The variable viscosity is assumed to vary as a inverse linear function of temperature and thermal conductivity as a linear function of temperature. Similarity transformations of the governing partial differential equations are obtained using Lie scaling group transformations. These similarity equations are solved numerically by using the Shooting technique. The numerical results for the non-dimensional velocity, temperature and concentration are displayed graphically for different values of variable viscosity, thermal conductivity, thermal dispersion and solutal dispersion. Local heat and mass transfer are shown in a tabular form. The present results are compared with previously published work and are found to be in good agreement.